EVALUASI PROGAM KELAS IBU HAMIL DALAM MENINGKATKAN PENGETAHUAN PERAWATAN PAYUDARA DI DESA BOROWETAN KECAMATAN BANYUURIP KABUPATEN PURWOREJO - Chandra Wulandari, Fetty; Febriyanti, Vina (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2025)
Pregnant women's classes are group learning activities that use the KIA book to discussthe health of pregnant women. Breast care is very important for those in society who wantto support exclusive breastfeeding. To assess the Evaluation of the Pregnant Mothers'Class Program in Improving Breast Care Knowledge in Borowetan Village. The causeand-effect variables are measured or collected simultaneously in the cross-sectionalmethod used in this research. Conducted in July 2024 in Borowetan Village, BanyuuripDistrict, Purworejo Regency, using Total Purposive Sampling with 40 respondents. A Pvalue of 0.000 was obtained, which is less than 0.05, indicating that there is a significantdifference between the pre-test and post-test, or that there is a significant effect. There isa significant correlation between maternal knowledge and the frequency of classes forpregnant women with an increase in the difference in average scores obtained from thepre-test and post-test of 39.60. It is hoped that this will enhance the source of knowledgeand broaden the understanding of pregnant women so that they better comprehend theskills for breast care during pregnancy.